(untitled) (European Journal of Formal Sciences and Engineering, 2022)
In recent years, qualitative research has gained ground as one of the main tools to analyze reality and propose innovation projects.This qualitative methodology has strengthened an innovative pedagogical structure, within the teaching of design disciplines.This is the specific case of our educational activity in the Modular System (UAM X), which facilitates the application of these tools in the design process. Reviewing the data in the analysis in a more qualitative way, promotes a more credible, reliable and valid vision to propose solutions to the problems detected.Thus, achieving a comprehensive understanding of the phenomenon and considering the factors involved in order to generate more relevant solutions.Within architecture, some projects that are addressed, such as the historical and cultural heritage of spaces and cities, use qualitative research techniques to discover and interpret the real vision of the inhabitant/ visitor of these spaces. It is essential to understand how the city is lived from the point of view of the different actors that interact in the space, in order to generate plans and projects that reinforce and enrich social interaction.In industrial design, the students take these tools and apply them to the first phase of their project in search of insights that will allow them to bring forward innovative products with a real impact on society.This paper addresses these two cases, highlighting the importance of these tools being internalized by our students completing their training with a research profile focused on design.